Metabolic and Nutritional Responses of Contrasting Aluminium-Tolerant Banana Genotypes Under Al Stress - Xinran Wu; Shahbaz Khan; Yucheng Qi; Chuanling Zhang; Sumera Anwar; Liyan Yin; Jiaquan Huang (Plants)
Aluminum (Al) toxicity is a major constraint to crop productivity in acidic soils, frequently encountered in banana-growing regions. This study investigates physiological and biochemical responses to Al stress in two Cavendish banana genotypes, Baodao and Baxi (Musa acuminata L.), which exhibit contrasting levels of Al tolerance. Banana plantlets were grown hydroponically under three AlCl3 concentrations (0, 100, and 500 μM) for 24, 48, and 72 h. Root elongation was progressively inhibited with increasing Al concentrations, with Baodao showing greater inhibition than Baxi. Al primarily accumulated in roots and displayed genotype-specific distribution patterns: Baodao concentrated more Al in root tips, suggesting lower exclusion efficiency. In contrast, Baxi, the Al-tolerant genotype, translocated Al from roots to shoots more effectively, indicating potential sequestration mechanisms in less sensitive tissues. Al stress influenced enzyme activities, with Baxi exhibiting higher phosphoenolpyruvate carboxylase and citrate synthase activities at 100 µM Al, while both genotypes showed similar reductions at 500 µM. Baodao experienced more pronounced reductions in H+-ATPase activity. At 100 µM Al, Baxi retained higher levels of key nutrients (P, Zn, Mg, Mn, Fe, K, and B) in essential tissues than Baodao. However, nutrient levels were reduced in both genotypes at 500 µM Al. These findings highlight Baxi’s superior resilience under Al stress, making it a suitable genotype for cultivation and breeding in acidic soils.